Complex externalities: introduction to the special issue - Paniagua, Pablo; Rayamajhee, Veeshan; Murtazashvili, Ilia (Public choice, 2024)
This paper introduces the special issue on complex externalities and public choice. The collection of essays extends analytical bridges between public choice, property rights economics, and new institutional economics. The essays question many of our prevailing assumptions behind the standard conceptualization of externalities. They also offer pragmatic and theoretical alternatives and apply these insights to analyze radio spectrum, environmental pollution, intellectual property, and public health issues. These essays demonstrate the ongoing significance of public choice in addressing society’s most pressing challenges.